2014
DOI: 10.4162/nrp.2014.8.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low water intake among South Korean adolescents - Korea National Health and Nutrition Examination Survey, 2007-2010

Abstract: Water is essential for life and plain water instead of sugar-sweetened beverages is one approach for decreasing energy intake. Due to limited data on characteristics associated with water intake among Korean adolescents, this study examined associations of demographic and behavioral characteristics with plain water intake by using nationally representative sample of South Korean adolescents. The data (2007-2010 Korea National Health and Nutrition Examination Survey) for 1,288 high school-aged adolescents (15-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…After the full text screening, we identified 15 articles reporting results from 13 studies that fulfilled all inclusion criteria. Among those, there was one interventional study with results reported in three articles (26)(27)(28), three observational longitudinal studies (29)(30)(31), and nine cross-sectional studies (32)(33)(34)(35)(36)(37)(38)(39)(40). We additionally included a cross-sectional analysis from one of the observational longitudinal studies (30), resulting in a total of ten cross-sectional analyses included in our review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the full text screening, we identified 15 articles reporting results from 13 studies that fulfilled all inclusion criteria. Among those, there was one interventional study with results reported in three articles (26)(27)(28), three observational longitudinal studies (29)(30)(31), and nine cross-sectional studies (32)(33)(34)(35)(36)(37)(38)(39)(40). We additionally included a cross-sectional analysis from one of the observational longitudinal studies (30), resulting in a total of ten cross-sectional analyses included in our review.…”
Section: Resultsmentioning
confidence: 99%
“…The renal solute load increases especially with increasing dietary salt and protein content . Representative studies in Australia, Korea, and the USA showed that total fluid or water consumption increased with sodium or salt intake in children and adolescents . In addition, sodium or salt intake per consumed food increased with increasing body weight status in children .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, inadequate hydration is an understudied health problem among college students in some geographic regions. 5 Water constitutes a greater proportion (about 60%) of the human body and plays a significant role in virtually all aspects of human life including disease prevention and health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…19 Above all, variations in cultural practices regarding water intake in healthy subjects is also contributory, making it difficult to compare results. 3 Although the consumption of beverages and foods contribute to total body fluid balance, water intake is known to contribute a greater proportion of the total body fluid. Therefore, water intake has a significant clinical bearing on the overall hydration status of individuals, due to the physiochemical properties and numerous health benefits of adequate water intake.…”
mentioning
confidence: 99%
“…Water is essential for life and plain water, instead of other caloric beverages, is one approached for decreasing energy intake (27), and therefore may play an important role to fight against obesity and metabolic syndrome. However, the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%